Decreasing CCT deviation of white light emitting diodes by employing SiO2 nanoparticles - My Hanh Nguyen Thi; Phung Ton That (Institute of Advanced Engineering and Science, 2021)
In this research, the SiO2 nano-particles (NPs) usage in enhancing optical performances of InGaN/GaN-based white light-emitting diodes (WLEDs) with remote phosphor structure. The research subject shows better lighting capacity than the white LEDs devices without the space between the layers. The adjustment in development process resulted in enhancements of internal quantum efficiency (IQE) and light extraction efficiency (LEE) that lead to 13.5% luminous efficacy improvement. From the experiments, it can be concluded that the LEE is affected by the trapped light and enhancing the light output with SiO2 scattering properties reduce the amount of trapped light. These results confirm that SiO2 nano-particles is effective in enhancing the optical performance of WLEDs and can be considered for production of higher quality devices.